USE OF THORACOEPIGASTRIC FLAP IN LARGE BREAST RESECTIONS: PHYLLODES TUMOR CASE REPORT - Pires, Douglas de Miranda; Souza, Guilherme Junqueira; Pace, Bárbara (Mastology, 2018)
Phyllodes tumors are uncommon fibroepithelial breast neoplasms capable of displaying a diverse range of biological behaviors. In their less aggressive form, they behave as benign fibroadenomas, although with a propensity to local recurrence after excision with satisfactory margins. On the other hand, they can metastasize, sometimes degenerating histologically into sarcomatous lesions. Phyllodes tumors represent less than 0.5% of all breast pathologies. They are smooth, multinodular, well-defined, firm, mobile, and painless masses of variable sizes, which can reach 40 cm in large tumors, with bright and stretched skin. When they progress to large tumor masses, they become a challenge to mastologists who need surgical satisfaction and coverage of the resected area. The use of thoracoepigastric flap has been an important surgical tool for these large breast lesions. The present study describes a case report of a large malignant phyllodes tumor that used the thoracoepigastric flap for coverage and closure.